2022
DOI: 10.3390/plants11141896
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Morphological Features and Essential Oil Content of Basils (Ocimum basilicum L.) Grown under Different Conditions

Abstract: This study was carried out in the experimental field and in unheated greenhouses of the Lithuanian Research Centre for Agriculture and Forestry Institute of Horticulture. The investigation aimed to evaluate the morphological features, amount of essential oil, and productivity of 10 basil (Ocimum basilicum L.) cultivars grown under different growing conditions. Studied cultivars were different according to morphological parameters, productivity, and the accumulation of essential oil. Most of the investigated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As a polymorphic species, Ocimum gratissimum exhibits a broader range of morpho-chemical traits, including plant height and fresh herb yield spanning from 46 to 123 cm and 98 to 618.3 g/plant, respectively [ 5 , 36 , 37 , 38 , 39 ], consistent with our own findings. In the case of Ocimum basilicum cultivars, previous research has shown variability in height (29.2 to 100 cm), canopy diameter (24.9 to 97.7 cm), and fresh yield (140 to 634 g/plant), influenced by factors such as growing conditions, cultivation seasons, geographical location, and specific cultivars [ 5 , 29 , 30 , 37 , 40 ]. Notably, ‘Fino Verde’ of O. basilicum exhibited a height of over 60 cm and a fresh herb yield exceeding 550 g/plant, contrasting with our findings [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a polymorphic species, Ocimum gratissimum exhibits a broader range of morpho-chemical traits, including plant height and fresh herb yield spanning from 46 to 123 cm and 98 to 618.3 g/plant, respectively [ 5 , 36 , 37 , 38 , 39 ], consistent with our own findings. In the case of Ocimum basilicum cultivars, previous research has shown variability in height (29.2 to 100 cm), canopy diameter (24.9 to 97.7 cm), and fresh yield (140 to 634 g/plant), influenced by factors such as growing conditions, cultivation seasons, geographical location, and specific cultivars [ 5 , 29 , 30 , 37 , 40 ]. Notably, ‘Fino Verde’ of O. basilicum exhibited a height of over 60 cm and a fresh herb yield exceeding 550 g/plant, contrasting with our findings [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Ocimum basilicum cultivars, previous research has shown variability in height (29.2 to 100 cm), canopy diameter (24.9 to 97.7 cm), and fresh yield (140 to 634 g/plant), influenced by factors such as growing conditions, cultivation seasons, geographical location, and specific cultivars [ 5 , 29 , 30 , 37 , 40 ]. Notably, ‘Fino Verde’ of O. basilicum exhibited a height of over 60 cm and a fresh herb yield exceeding 550 g/plant, contrasting with our findings [ 40 ]. Furthermore, green holy basil hand height varies from 37.3 to 71.9 cm with a canopy spread of 50 to 67.3 cm [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basil essential oil (BEO) has been extensively studied, and its composition is known to vary depending on the plant’s phenological stage and chemotype [ 26 , 27 , 28 ]. Different BEO chemotypes have been identified based on the predominant constituents (e.g., linalool, methyl chavicol (estragole), methyl eugenol, eugenol, citral, or α-bergamotene) [ 26 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a difference in the chemical composition of O. basilicum essential oils depending on the plant variety, harvesting season, soil and climate conditions, growing technology, and postharvest processing, etc. [25][26][27]. The chemical composition and biological activity of O. basilicum essential oils depend on environmental conditions and location, seasonal variation, different agronomic and harvesting techniques, and drying and processing methods [23].…”
Section: Introductionmentioning
confidence: 99%